INTERPRETASI SANTO PAULUS TENTANG PERKAWINAN DAN SELIBAT MENURUT 1 KORINTUS 7 - Siku Jata, Yohanes Fransiskus (STP St. Bonaventura Medan, 2020)
This article to briefly introduce Paul's views on Marriage and Seeness (1 Corinthians 7). As a native Jew, Paul was carefully educated to understand the religion and culture of his ancestors. In this regard about himself he said: